Local Distortions in Parental Beliefs over Child Skill - Kinsler, Josh; Pavan, Ronni (Journal of Political Economy, 2021)
Using data from the Early Childhood Longitudinal Study–Kindergarten Class of 1999, we show that parental beliefs about a child’s cognitive skill relative to children of the same age are distorted by a child’s cognitive skill relative to children in the same school. Parents of children attending schools with low (high) average skills tend to believe their child is higher (lower) in the overall skill distribution than they actually are. Teacher evaluations of child skill also exhibit local distortions, providing a channel through which parental biases might arise. Finally, we relate parental beliefs and investment, providing insight on how local distortions may impact the skill distribution.